PENGARUH KEPRIBADIAN GURU DAN PROFESIONALISME GURU TERHADAP PRESTASI BELAJAR SISWA KELAS X SMA NEGERI 2 PEMATANG SIANTAR - Muammar Rinaldi; Nanda Fridani (LPPM STIE EKA PRASETYA, 2019)
The This research was conducted to investigate whether there is an influence of teacher personality and teacher professionalism on student achievement in tenth-grade IPS 2 students of SMA Negeri Pematang Siantar. The population in this study were all students of tenth-grade IPS SMA Negeri 2 Pematang Siantar, totaling 188 people. The sampling technique in this study used a random sampling method of 64 students. Data collection techniques used were observation, questionnaires, and documentation. The validity test for item questionnaire analysis used the product-moment correlation formula, and the reliability was calculated using the Cronbach alpha formula. Data analysis techniques used were multiple linear regression, t-test, F test and test determination (R2). The value of determination (R2), the contribution of teacher personality variables and teacher professionalism to student achievement, is 14.7%. The rest is influenced by other variables that are outside the analysis of this study. It can be concluded that the teacher's personality has a positive and significant influence on student achievement. Whereas teacher professionalism did not have a positive and significant influence on student achievement in tenth-grade students IPS SMA Negeri 2 Pematang Siantar.